1995
DOI: 10.1093/infdis/172.5.1324
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of an Outer Surface Protein A Vaccine in Subjects with Previous Lyme Disease

Abstract: The safety and immunogenicity of a recombinant outer surface protein A (OspA) Lyme vaccine in patients previously diagnosed with Lyme disease was assessed in a dose-ranging, prospective study. Thirty healthy volunteers were consecutively assigned to receive three doses of 3, 10, or 30 micrograms of OspA vaccine at 0, 1, and 2 months. Subjects were seen 3 days after each vaccine dose and 1 month after completion of the three-dose schedule. Local side effects included soreness, induration, swelling, and redness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 14 publications
0
25
0
1
Order By: Relevance
“…burgdorferi antibodies, in particular anti-OspA antibodies, may be protective in Lyme disease; however, even healthy patients vaccinated with an OspA-containing formulation developed transient arthralgia (34). However, a reactive arthritis was not a universal finding in the OspA vaccine recipients (42).…”
Section: Discussionmentioning
confidence: 99%
“…burgdorferi antibodies, in particular anti-OspA antibodies, may be protective in Lyme disease; however, even healthy patients vaccinated with an OspA-containing formulation developed transient arthralgia (34). However, a reactive arthritis was not a universal finding in the OspA vaccine recipients (42).…”
Section: Discussionmentioning
confidence: 99%
“…species (Barbour et al 1984). A recombinant vaccine has been developed on the basis of this antigen (Schoen et al 1995). Considering the low level in horizontal plasmid transmission (Dykhuizen et al 1993), we used the OspA gene sequence to investigate the phylogenetic relationship between our samples and the sequences available in GenBank to infer population structure.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that prior infection with B. burgdorferi sensu lato might blunt the immune response, resulting in a lower ability of seropositive subjects to mount an immune response to vaccination with OspA (26,27). Alternatively, because of the lipidated nature of the OspA vaccine and the high expression of lipoproteins by B. burgdorferi sensu lato, it is possible that the anti-lipoprotein antibodies induced in seropositive subjects by previous infection interfere with the induction of antibody responses against the OspA vaccine, such that higher antigen doses are required in the seropositive population.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study of a monovalent OspA-1 vaccine investigated the antibody responses to vaccination in seropositive subjects, but this study did not include a head-to-head seronegative cohort (27). Because of the lack of a direct comparator group in this previous study and the use of a different assay format than those in studies on the same vaccine in seronegative populations (28)(29)(30)(31)(32)(33), it is not clear whether the previous monovalent OspA-1 vaccine induced similar antibody titers in seronegative and seropositive populations.…”
Section: Discussionmentioning
confidence: 99%